Research progress of acupuncture rehabilitation nursing for stroke patients (脑卒中患者针刺康复护理研究进展) - HUANG Chaoping (黄朝萍); GENG Qingwen (耿庆文) (中西医结合护理)
Given the increasing number of aging population in china, the rehabilitation nursing for stroke patients has been becoming the focus of attention in china. The Traditional Chinese Medicine acupuncture is proved to be an effective treatment of stroke and its sequelae. This paper reviewed studies on acupuncture rehabilitation nursing interventions for stroke patients in perspectives of cephalic acupuncture, body acupuncture and its combination with modern rehabilitation technologies, and provided reference for post-stroke rehabilitation practice. (随着人口老龄化趋势加重, 脑卒中患者的康复护理成为社会关注的重点。针刺治疗脑卒中及后遗症效果明确。本研究就头针、体针以及头体针联合现代康复在脑卒中康复干预中的应用现状进行综述, 旨在为促进脑卒中患者的功能康复提供参考。)